Penerapan Model Pembelajaran Kooperatif Tipe Numbered Head Together Untuk Meningkatkan Hasil Belajar IPS Siswa Kelas V SD Negeri 57 Parepare - Hasnah Hasnah; Fajar Fajar; Syafruddin Syafruddin (Prodi PGSD FIP UNM, 2017)
The problem in this research is the low learning outcomes Social Sciences. The problems that were examined, namely How did the process of implementing a model of cooperative-type Numbered Head Together in social studies materials Struggle Maintaining Independence of Indonesia in class V?, Is the application of models of cooperative-type Numbered Head Together to improve learning outcomes IPS materials Struggle Maintaining Independence of Indonesia in Class V ?. The purpose of this study was to determine the type of cooperative learning application process Numbered Head Together social studies in Class V and to find out the learning outcome IPS after the implementation of cooperative learning type Numbered Head Together graders V. The approach used was qualitative approach using Type Research Class action. The focus of this study focused on the current implementation process focus on social studies learning by implementing measures NHT comprising the step numbering, ask questions, think together and answer as well as focus on the results of student learning outcome social studies on Maintaining Independence Struggle Indonesia. The subjects were teachers and students of class V, as many as 24 people, consisting of 10 men and 14 women. Data collection techniques used are tests, observation and documentation. Analysis of the data used is descriptive qualitative data analysis by classifying the data Aspect Aspect Teachers and Students. The learning outcomes of students in the first cycle of less qualified because they are indicators of unmet ie the number of students who were able to take the test is given to the right is still small, but on the second cycle results are increased and qualified Good. Conclusion of the study, namely an increase learning outcomes in social studies about the struggle of Indonesian Independence Maintain through the application of models Pembelejaran Cooperative Numbered Head Together in Class V SD Negeri 57 Parepare.Keyword: Numbered Head Together, learning outcomes